1986
DOI: 10.1149/1.2108569
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagrams and Conductivity Characterization of Some  PEO  ‐ LiX Electrolytes

Abstract: PEO‐normalLiX false(X=CF3SO3−,ClO4−,and AsF6−false) systems have been characterized by x‐ray diffraction and optical microscopy, and the resulting phase diagrams are taken into account for the interpretation of ac impedance measurements. Eutectic reactions and multiple‐intermediate‐compound formation are characteristic of most systems. Simple phenomenological models do not explain the overall conductivity behavior. The activation energy of ion transport is independent of the anion, and remains mainly constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
321
6
4

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 449 publications
(368 citation statements)
references
References 15 publications
37
321
6
4
Order By: Relevance
“…a pure capacitor is a straight line parallel to the imaginary axis (Z ), whereas in a real case, the observed steep rising response owes to the electrode-electrolyte interface. The conductivity measurement on each composition is shown in figure 8, which is the indicative that the composition (PEO 70 AgI 30 ) 70 (AC) 30 has highest conductivity (σ ∼ 1.926 × 10 −3 S cm −1 ), and this composition is used as an electrode for each symmetric capacitor and referred to as PAC(OCC). …”
Section: 1d Electrochemical Behaviour Of Peo-based Electrodementioning
confidence: 99%
See 2 more Smart Citations
“…a pure capacitor is a straight line parallel to the imaginary axis (Z ), whereas in a real case, the observed steep rising response owes to the electrode-electrolyte interface. The conductivity measurement on each composition is shown in figure 8, which is the indicative that the composition (PEO 70 AgI 30 ) 70 (AC) 30 has highest conductivity (σ ∼ 1.926 × 10 −3 S cm −1 ), and this composition is used as an electrode for each symmetric capacitor and referred to as PAC(OCC). …”
Section: 1d Electrochemical Behaviour Of Peo-based Electrodementioning
confidence: 99%
“…In the present paper, the ionic conducting solid polymer electrolyte prepared by the addition of inorganic oxide fillers Al 2 O 3 and SiO 2 to the standard SPE (PEO 70 AgI 30 ) system has been reported. The synthesized nanocomposite solid polymer electrolyte has been characterized by several analytical techniques, such as differential scanning calorimetry (DSC) and thermogravimetric (TGA) studies, electrical studies such as conductivity and transport number measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that many of these ionically conducting materials are not single phase and phase diagram investigations reveal the presence of ] more than one compound (4,5,6). It has also been shown for the PEOLiBF, system that allotropes exist depending upon the solvent used -(7 .…”
Section: I13bmentioning
confidence: 99%
“…Phase diagrams for a number of alkali metal salt-PEO systems have been established (4,5,6,(14)(15)(16)(17) All subsequent handling of the materials was carried out in a <1% RH dry room. All of these lithium salts and tne PEO dissolve fairly easily in acetonitrile and films were cast from this solvent.…”
Section: -mentioning
confidence: 99%